PATH ANALYSIS BETWEEN CONSTRUCTS OF TECHNOLOGY ACCEPTANCE MODEL (TAM) (A CASE STUDY ON RECEIPT OF VIRTUAL ARMS SOLUTION FTS D - 423 IN INDONESIAN EASTERN FLEET TRAINING COMMAND) - Ikhwan Syahtaria; Ahmadi Ahmadi; Bambang Suharjo; Pius Herdasa Krisna Murti (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
Indonesian Eastern Fleet Training Command currently has the facilities to train professional soldiers in the shooting.A simulator facility in the form of computer-based clinic shooting is called Virtual Arms Solution FTS D-423 (VAS).Need to analyse the relationship between perceived ease of use and usefulness of VAS in order to determine thelevel of acceptance. Both these factors are modelled by the Technology Acceptance Model (TAM) which canexplain the factors that influence the actual receipt of the use of technology. After that, the relationship between thetwo factors that have been modelled with the Technology Acceptance Model to be treated using Path Analysis(Path Analysis). Where the path analysis was used to analyse the causal relationships between variables in order todetermine the effect of the direct and indirect causes of the variable to a variable result. Based on the analysis anddiscussion, it is obtained as follows that the ease and usefulness of a positive effect on Attitude using VAS positiveeffect on Behavioural Intention using VAS. Behavioural intentions affect the Actual Usage.Keywords: Virtual Arms Solution, Technology Acceptance Model, Path Analysis.